XOG 3 EVENT PROMOTION MEDIA DESIGN IN BUKITTINGGI CITY - Wendo Afriyoma Pratama; Lucky Adhitya (Journal Informatic, Education and Management (JIEM), 2026)
The design of promotional media for the XOG 3 event was developed to build a strong brand image and strengthen solidarity among Yamaha Xmax user communities across Indonesia. The organization of XOG 3 also serves as a strategic platform to promote the City of Bukittinggi as the official host, while shaping public perceptions, emotions, associations, and expectations among Yamaha Xmax users nationwide. Using the SWOT analysis method, a relevant and strategic image concept was formulated for the promotional media design of the XOG 3 event in Bukittinggi. The event was branded with the title “Badunsanak Salamonyo,” a phrase that resonates strongly with local cultural identity and is expected to create immediate recognition of Bukittinggi among the target audience. The primary objective of designing the promotional media for XOG 3 is to establish a distinctive identity closely connected to Bukittinggi. This identity is intended to foster pride among local residents, stimulate economic growth, and differentiate Bukittinggi from other cities. Furthermore, the promotional media design for XOG 3 functions not only as event branding but also as a tourism promotion tool for Bukittinggi. By highlighting its natural landscapes, historical heritage, culinary richness, and cultural uniqueness, the event is expected to increase tourism visits and strengthen the city’s position as a leading tourism destination, ultimately contributing to the improvement of the local economy.